Kajian Beberapa Cara Fermentasi yang Dilakukan oleh Petani terhadap Mutu Biji Kakao (Theobroma cacao L.) - NI LUH MADE PRADNYAWATHI; I KETUT ARSA WIJAYA; I NYOMAN SUTEDJA; ANAK AGUNG MADE ASTININGSIH (Fakultas Pertanian Universitas Udayana, 2018)
Study of Assorted Fermentation Methods Conducted by Local Farmers on the Quality of VCocoa Beans (Theobroma Cacao L.). Various fermentation methods have been done by local farmers, however there has been no report on the quality of cocoa beans from those methods. This study aims were to identify various ways of cocoa beans fermentation conducted by local farmers; to compare between quality of fermented beans produced by local farmers and suggested quality of fermented beans; and o obtain a simple fermentation method which resulted in good quality beans and suitable practice for local farmers. The research wasconducted in Tabanan Regency, Province of Bali through field survey with observation and interview method, and supported with literature study. According to field observation and analysis of fermented cocoa beans taken from the local farmers, it can be concluded that most of local farmers did not fermented their kakao seeds. Thus, the fermentation done by utilizing a plastic sack, a bamboo basket or a wooden box lined and covered with banana leaves. The research also found that implementing similar fermentation methods to the seed did not always resulting similar quality of cocoa beans. Finally, the simplest method for local farmers to ferment the cocoa seed was the fermentation by utilizing basket lined and covered with banana leaves with at least 90kg wet beans.